COMMUNITY PARTICIPATION PATTERN IN THE PLANNING OF ISLAMIC EDUCATION FUNDING IN TAMAN PENDIDIKAN AL-QUR’AN(TPQ) IN BANYUMAS REGENCY, CENTRAL JAVA, INDONESIA - Sunhaji, Sunhaji; Purnomo, Sutrimo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2020)
This study was aimed at examining the pattern of community participation in the planning of Islamic education funding, especially in the Taman Pendidikan Al Qur'an (TPQ). This research is important because many Islamic educational institutions had low standard quality and even stopped their activities because of weak education funding, including in the realm of financial planning. Community participation is considered appropriate for strengthening education financing planning as a form of equitable democracy, which means that the community has the right to get quality education and is obliged to provide funds. This research is qualitative descriptive field research with case studies as its approach. Data collection techniques used were observation, interviews, and documentation, while the analysis of this research follows the stages of data reduction, data presentation, and inference. The obtained data shows that the presence of active community participation with cultural religious functional patterns in the planning of Islamic education financing at TPQ in Banyumas Regency, Central Java indicates an increase in awareness and serious attention of the community towards religious education for their children. Therefore, it is time for Islamic education institutions to be able to utilize this momentum as part of efforts to improve the quality of Islamic education through strengthening education funding. Keywords: Community Participation, Education Funding, and Islamic Education